Kecerdasan Spiritual dalam Kurikulum ISMUBA di SMA Muhammadiyah Imogiri: Penyelarasan dengan SDG 4 dan Peningkatan Kesejahteraan Siswa - Nurul Hidayah; M. Syahrul Qhodi Alam; Ichsan Ichsan; Sibawaihi Sibawaihi; Samoth Phanichharath (Fakultas Tarbiyah dan Ilmu Keguruan UIN Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2025)
This study aimed to develop a conceptual model for fostering students’ spiritual intelligence through the ISMUBA curriculum at SMA Muhammadiyah Imogiri, Indonesia, with a focus on promoting sustainable educational practices in alignment with Sustainable Development Goal 4 (Quality Education). It employed a qualitative case study design and purposive sampling; participants comprised students from grades X–XII, ISMUBA teachers, and school management as key informants. Data were collected through semi-structured interviews, participant observation, and documentary analysis of the curriculum and school programs. Thematic analysis was used to identify patterns in the integration of spiritual values, and findings were linked to theories of spiritual intelligence and Islamic education through literature synthesis. The results revealed that the six ISMUBA subjects Al-Qur’an and Hadith, Aqidah Akhlak, Fiqh, History (Tarikh), Muhammadiyah Studies, and Arabic collectively enhanced students’ transcendental awareness, meaning-making, ritual discipline, empathy, and social responsibility, all of which contribute to the realization of SDG 16 (Peace, Justice, and Strong Institutions). The proposed model explained implementation mechanisms such as interactive-reflective approaches, teacher exemplarity, habitual religious practices, and adaptation to contemporary issues. The implications of this research provide a practical framework for Muhammadiyah educators and curriculum developers to strengthen the spiritual dimension in teaching.